Gambaran Drug Related Problems (DRPs) Terapi Farmakologi Pasien ISPA Pediatrik di Rumah Sakit PKU Muhammadiyah Gamping Yogyakarta - Husna, Nadia; Padmasari, Siwi (Jurnal Kesehatan Andalas, 2021)
Acute Respiratory Infection has become the major cause of death in children in developing countries. There were about 11.9 million episodes of severe acute lower respiratory infection that resulted in hospital admission in young children worldwide. The method of drug administered was the common Drug-Related Problems found in young children. Objectives: To evaluated Drug-Related Problems of Acute Respiratory Infection drug therapy in pediatric patients. Methods: Ninety-four pediatric patients were included in this study. Drug therapy data were obtained from medical records from January 2018 until July 2019, as this study was using a retrospective method. Drug-Related Problems of drug therapy were analyzed based on the Cipolle classification system. Results: Prevalence of female and male patients are in the same number (50%) with the highest prevalence on 2-11 years (72.34%) in young children. The number of Drug-Related Problems was found about 61.49% from 148 numbers of used drugs with improper drug selection as the major Drug Related Problems (51,65%)Â  followed by drugs without indication and underdose by 23.08% and 15.38%, respectively.Keywords: Â acute respiratory infection, hospital, pediatrics, pharmacologic therapy